Late Paleozoic–early Mesozoic continental biostratigraphy — Links to the Standard Global Chronostratigraphic Scale - Schneider, Joerg W.; Lucas, Spencer G.; Scholze, Frank; Voigt, Sebastian; Marchetti, Lorenzo; Klein, Hendrik; Opluštil, Stanislav; Werneburg, Ralf; Golubev, Valeriy K.; Barrick, James E.; Nemyrovska, Tamara; Ronchi, Ausonio; et al. (Palaeoworld, 2020)
Nonmarine biostratigraphic/biochronologic schemes have been created for all or parts of the late Carboniferous–Middle Triassic using palynomorphs, megafossil plants, conchostracans, blattoid insects, tetrapod footprints and tetrapod body fossils, and these provide varied temporal resolution. Cross correlation of the nonmarine biochronologies to the Standard Global Chronostratigraphic Scale has been achieved in some parts of the late Carboniferous–Middle Triassic in locations where nonmarine and marine strata are intercalated, the nonmarine strata produce biochronologically significant fossils and the marine strata yield fusulinids, conodonts and/or ammonoids. Other cross correlations have been aided by magnetostratigraphy, chemostratigraphy and a growing database of radioisotopic ages. A synthetic nonmarine biochronology for the late Carboniferous–Middle Triassic based on all available nonmarine index fossils, integrated with the Standard Global Chronostratigraphic Scale, is presented here. The focus is on the nonmarine biostratigraphy/biochronology of blattoid insects, conchostracans, branchiosaurid amphibians, tetrapod footprints and tetrapod body fossils within the biochronological framework of land-vertebrate faunachrons. Correlation to the Standard Global Chronostratigraphic Scale presented here is divided into seven time intervals: Pennsylvanian, Carboniferous–Permian boundary, Cisuralian, Guadalupian, Lopingian, Permian–Triassic boundary and Early to Middle Triassic. The insects, conchostracans and branchiosaurs provide robust nonmarine correlations in the Pennsylvanian–Cisuralian, and the footprints and tetrapod body fossils provide robust correlations of varied precision within the entire Pennsylvanian–Middle Triassic. Radioisotopic ages are currently the strongest basis for cross correlation of the nonmarine biostratigraphy/biochronology to the Standard Global Chronostratigraphic Scale, particularly for the Pennsylvanian–Cisuralian. Chemostratigraphy and magnetostratigraphy thus far provide only limited links of nomarine and marine chronologies. Improvements in the nonmarine-marine correlations of late Paleozoic–Triassic Pangea require better alpha taxonomy and stratigraphic precision for the nonmarine fossil record integrated with more reliable radioisotopic ages and more extensive chemostratigraphic and magnetostratigraphic datasets.